The BUGS book : a practical introduction to Bayesian analysis /: a practical introduction to Bayesian analysis. ([2012]) - Lunn, David, 1971-; Jackson, Christopher (Christopher Hamilton); Best, Nicky; Thomas, Andrew; Spiegelhalter, D. J
No abstract available